DIFFERENCE BETWEEN DENSTISTS’ AND LAY PEOPLE’S ESTHETIC PERCEPTION IN THE VARIATIONS OF VERTICAL PROPORTION OF LOWER FACIAL THIRD ON DEUTERO MALAY RACE - Nabilah Aulia Fitri; Nur Indrawati Lipoeto; Yuri Deswita (Faculty of Dentistry Universitas Andalas, 2015)
The aim of this study was to determine the differences in perception between dentists and lay people in the variations of vertical proportion of lower facial third on Deutero Malay race. This was an analytic comparative study with cross sectional design. Facial profile photo of woman with normal lower facial third were modified digitally by increasing and decreasing her Sn-Me height by interval of 5% to obtain 5 variations of proportion. Twenty-eight dentists and 28 lay people (25-59 years) scored each photo using Visual Analogue Scale (VAS). In conclusion, there were significant differences between dentists and lay people perception regarding evaluation criticality toward vertical proportion of lower facial third in facial profile, but dentists and lay people show the same preference for vertical proportion of lower facial third.